PEMBERIAN KOLKISIN TERHADAP PERTUMBUAN DAN HASIL TANAMAN KEDELAI HITAM (Glycine max (L.) merr) - Fathurrahman Fathurrahman (UIR Press, 2015)
The aim of this research is to determine the effect of colchicine on growth and yield the black soybean for cikurai varieties. The research was conducted at the field trials Faculty of Agriculture, Universitas Islam Riau. The experimental design used was a completely randomized design (CRD) factorial with two factors, the first factor was the concentration of colchicine (K factor) which consisted of 4 levels K0 (0%), K1 (0.01%), K2 (0.05%), K3 (0.1%). The second factor was the soaking time (factor P) which consisted of 4 levels: P1 (3 hours), P2 (6 hours), P3 (12 hours) and P4 (18 hours). The results showed that the interaction of colchicine concentration and soaking significantly on the parameters of the seed crop was heavy concentration of 0.1% and eighteen hours to soaking (K3P4) produced a means 30.87 grams. The highest concentration of singly significantly in treatment K3 (0.1%), all parameters of flower, plant height, seeds weight and heavy planting 100 seeds. While soaking treatment for a single parameter significantly affected flower and seed weight cultivation on P4 (18 hours).